2008
DOI: 10.1007/s10661-007-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater corrosiveness for unconfined aquifer system at Kalpakkam

Abstract: Groundwater samples from the shallow unconfined aquifer were collected from fifteen borewells in Kalpakkam nuclear plant site and were analysed for various physico-chemical parameters. The pH, temperature, salinity, TDS and EC were measured in the field. The borewell samples were analysed in the laboratory for Ca(2+), Mg(2+), Na(+), Cl(-), CO(2-)(3), HC(O-)(3), N(O-)(3) and SO(2-)(4). The Piper Trilinear diagram showed that majority of the borewell samples fall in Na - Cl +SO(4) type and Na - CO(3)+HCO(3) type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Out of the 12 borewells, BW6, BW7, BW8 and PBW1 were brackish type and all the other 8 wells were of freshwater type. Similar observations were made by Sasidhar and Vijayakumar (2008).…”
Section: Groundwater Analysissupporting
confidence: 89%
“…Out of the 12 borewells, BW6, BW7, BW8 and PBW1 were brackish type and all the other 8 wells were of freshwater type. Similar observations were made by Sasidhar and Vijayakumar (2008).…”
Section: Groundwater Analysissupporting
confidence: 89%
“…As the temperature decreases, the maximum salt solubility also decreases (Helber et al 2012; Bingham et al 2010), which causes seawater to exhibit lower conductivity and higher electrolyte resistivity (Sharqawy 2013; Sasidhar and Vijay Kumar 2008). The lower the temperature is, the greater the oxygen solubility in water is and the greater the corrosion rate may be.…”
Section: Methodsmentioning
confidence: 99%
“…However, the anions were present simultaneously under a natural condition. Previous studies have indicated that the higher the value of LI, the higher the corrosiveness of water [36]. After a chemical analysis of the experiment water, the tendency release iron was analyzed by the LI index.…”
Section: Resultsmentioning
confidence: 99%